Gut microbiota dysbiosis in infantile cholestatic hepatopathy - Zou, Yi; Ni, Wenhao; Zhou, Yong; Sun, Dan; Chen, Feng; Li, Xianyun (Frontiers in Pediatrics, 2025)
BackgroundCholestatic hepatopathy is common in infants. While many studies link gut microbiota to liver and gallbladder diseases, the relationship between infantile cholestatic hepatopathy (ICH) and gut microbiota remains unclear.MethodsWe collected stool samples from 19 healthy controls and 33 infants with ICH aged ≤3 months, then determined the intestinal microbiota by 16S rDNA sequencing. The differences of microbiota structure and functional between the two groups were analyzed.ResultsAlpha-diversity analysis showed that the Chao1 and ACE indexes were significantly higher in the ICH group than control group (p < 0.05). LEfSe analysis showed that 18 bacteria taxa, including Streptococcus, Streptococcaceae, and Staphylococcales, enriched significantly in the ICH group, and 3 bacteria taxa were enriched in the control group. At the genus level, the relative abundance of Streptococcus, Escherichia-Shigella, and Lactobacillus in ICH group was higher than control group (p < 0.05). The Receiver Operating Characteristic (ROC) analysis demonstrated that Streptococcus was highly valuable in distinguishing ICH from healthy controls. Moreover, functional prediction analysis identified 59 metabolic pathways potentially associated with ICH.ConclusionGut microbiota dysbiosis is associated with infantile cholestatic hepatopathy, and Streptococcus can be used as an essential biomarker to identify ICH.